Mathematical Difficulties of 7th Grade MTs Students Analysis in Online Learning Based on The Realm Bloom’s Taxonomy - Heri Heri; Eva Dwi Minarti; Linda Linda (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
Online learning is a new alternative for the continuity of learning activities during the Covid-19 period, where learning is carried out online through various media or ICT used. This research aims to see the analyze how difficult students mathematical in working on mathematical problems, especially in quadrilateral and triangular material. The subject of this study were students of class VII at MTs Negeri Kabupaten Bandung Barat. The instrument used were written tests in the form of essays which numbered 5 questions and a student questionnaire via a google form. This research method uses descriptive analysis, to find out the student's mistakes in solving problems. Processing data is calculated in the form of average student scores obtained by analysis used on Taksonomi Bloom cognitive. The results showed that students achievement in the process of solving triangular and quadrilateral problems based on the stage of Taksonomi Bloom is based on the stage of Taksonomi Bloom, namely, at the cognitive stage the most is in stage C5 and C6 there is evaluation and creation, then in C2, C3, and C4 also still less than 60%. Thus it can be seen that the level of student understanding of rectangular and triangular material is still relatively low so that there is difficulty in solving students' problems on rectangular and triangular material based on Taksonomi Bloom stages. Keywords: student difficulties, online learning, quadrilateral, and triangular, taxonomy bloom